Surgical Correction of Isolated Discrete Sub-Aortic Membrane: A Case Report (Journal of Chittagong Medical College Teachers' Association, 2025)
The association between discrete sub-aortic membrane are frequently associated with other sub-aortic anomalies which is reported less often, and till today the surgical correction is considered challenging. An 18-year-old, young lady presented to us with the diagnosis of a discrete sub-aortic membrane producing severe Left Ventricular Outflow Tract Obstruction (LVOTO). We excised the membrane surgically and patient showed excellent symptom free recovery. Per-operative Trans-Esophageal Echocardiogram (TEE) and post-operative Transthoracic Echocardiogram (TTE) showed mild residual membrane and minimum LVOT pressure gradient.JCMCTA 2023 ; 34 (2) : 146-149